Method for catalyzing chiral boron addition reaction of alpha, beta, gamma, delta-unsaturated ketone by nano-composite microsphere supported copper material

By using nanocomposite microsphere-supported copper materials to catalyze the chiral boron addition reaction of α,β,γ,δ-unsaturated ketones, the problem of catalysts being unable to be recycled and unsuitable for industrial production in the prior art is solved, and high efficiency is achieved , environmentally friendly catalytic effect.

CN119390715APending Publication Date: 2025-02-07HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411410872.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the chiral boron addition reaction of catalyzed α,β,γ,δ-unsaturated ketones has problems such as severe environmental pollution, harsh reaction conditions, high cost, inability to recycle the catalyst, and unsuitable for large-scale industrial production. .

Method used

Using nanocomposite microsphere-supported copper material as a catalyst, 1,4-chiralization is obtained by performing chiral boron addition reaction with α,β,γ,δ-unsaturated ketone and pennadol biborate in the reaction solvent. Boron compounds. The catalyst is prepared from PS-CS-SiO2 nanocomposite microspheres loaded with Cu2+, and is recyclable and green and environmentally friendly.

Benefits of technology

It realizes efficient catalytic chiral boron addition reaction of α,β,γ,δ-unsaturated ketones, with yields up to 98%, enantioselectivity up to 96%. At the same time, the catalyst can be recycled and recycled multiple times, suitable for large-scale industrialization application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390715A_ABST
    Figure CN119390715A_ABST
Patent Text Reader

Abstract

The invention provides a method for catalyzing an alpha, beta, gamma, delta-unsaturated ketone chiral boron addition reaction through a nano-composite microsphere supported copper material, and belongs to the technical field of asymmetric catalyst.The method comprises the following steps that in a reaction solvent, alpha, beta, gamma, delta-unsaturated ketone chiral boron addition reaction is carried out, and alpha, beta, gamma, delta-unsaturated ketone chiral boron addition reaction is carried out; the preparation method comprises the following steps: carrying out chiral boron addition reaction on beta, delta-unsaturated ketone and B2 (pin) 2 under the action of a nano-composite microsphere loaded copper material and a chiral ligand to obtain a 1, 4-chiral boron compound; a carrier of the nano-composite microsphere loaded copper material is a PS-CS-SiO2 nano-composite microsphere, the PS-CS-SiO2 nano-composite microsphere is composed of PS monodisperse microsphere powder, SiO2 and chitosan, and an active component Cu < 2 + > is loaded on the PS-CS-SiO2 nano-composite microsphere. 3-7 mg of the nano composite microsphere loaded copper material is added into every 0.2 mmol of alpha, beta, gamma, delta-unsaturated ketone. The nano-composite microsphere loaded copper material is used as a catalyst to catalyze alpha, beta, gamma, delta-unsaturated ketones to perform chiral boron addition reaction, and the nano-composite microsphere loaded copper material is used as a novel catalytic material, can be recycled, and is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of asymmetric catalysis, and in particular to a nanocomposite microsphere-loaded copper material catalysis. α , β , c , d -Method for chiral boron addition reaction of unsaturated ketones. Background Art

[0002] In recent years, with the gradual deepening of research on organoboron compounds, more and more studies have proved that organoboron reagents are very practical organic synthetic building blocks and are often used as intermediates for the synthesis of drugs and bioactive molecules. As of June 2024, 5 boron-containing drugs have been approved for marketing worldwide, including bortezomib, tavaborole, ixazomib, criborole and faborbactam. This is mainly due to the fact that the boronate functional group can be easily transformed into a variety of ways, such as coupling, amination, oxidation, halogenation, etherification, etc. More importantly, in the process of boron's diverse transformation, the stereo configuration of its substrate can basically be well maintained. Based on this, asymmetric boron addition of unsaturated ketones provides an effective way to synthesize organoboron compounds, which has important research value.

[0003] In 2012, Santos' group reported the first Cu(II)-catalyzed α , β - The boron addition reaction of unsaturated ketones, using CuCl2 as catalyst and benzylamine or tetramethylethylenediamine (TMEDA) as solvent, can achieve a yield of up to 98%. In 2013, Kobayashi's research group further expanded the substrates of the boron addition reaction to α , β , c , d -unsaturated ketones, using Cu(OH)2 or Cu(OAc)2 as catalyst and pure water as solvent, the yield (yield) can reach up to 93%, the enantioselectivity (ee value) can reach up to 99%, and due to the Lewis acid properties of Cu(II), the products are all 1,4-addition, α , β , c , d - provides ideas for the regioselective transformation of unsaturated ketones.

[0004] According to existing research reports, the effective boron addition α , β , c , d-Unsaturated ketones have fewer reaction substrates, and the boron addition reactions reported so far are mostly homogeneously catalyzed. The catalysts are not biodegradable and recyclable, which does not conform to the development concept of green chemistry and is not suitable for large-scale industrial applications. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a nanocomposite microsphere-loaded copper material catalyst α , β , c , d -The method for chiral boron addition reaction of unsaturated ketones is intended to solve the technical problems in the prior art such as serious environmental pollution, harsh reaction conditions, high cost, inability to recycle catalysts, and unsuitability for large-scale industrial production.

[0006] In the first aspect, the present invention provides a nanocomposite microsphere-supported copper material catalyst. α , β , c , d - A method for chiral boron addition reaction of unsaturated ketones, comprising the following steps: in a reaction solvent, α , β , c , d -unsaturated ketone and biboric acid pinacol ester (B2(pin)2) undergo chiral boron addition reaction under the action of nanocomposite microspheres loaded with copper material and chiral ligand to obtain 1,4-chiral boron compound; the carrier of nanocomposite microspheres loaded with copper material is PS-CS-SiO2 nanocomposite microspheres, and the PS-CS-SiO2 nanocomposite microspheres are composed of PS monodisperse microsphere powder, SiO2 and chitosan. The active component Cu is loaded on the PS-CS-SiO2 nanocomposite microspheres 2+ , PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material were obtained; each 0.2mmol α , β , c , d -3~7 mg of nanocomposite microsphere-loaded copper material is added to the unsaturated ketone.

[0007] In the technical solution of the embodiment of the present application, nanocomposite microspheres loaded with copper material are used as catalysts. α , β , c , d -Unsaturated ketones undergo chiral boron addition reaction, and nanocomposite microspheres loaded with copper materials are used as new catalytic materials, which are recyclable and environmentally friendly.

[0008] In addition to the characteristics of small particle size, large specific surface area, strong adsorption, good dispersibility, easy modification and modification, polystyrene (PS) monodisperse microsphere powder also exhibits good stability, strong hydrophobicity and low adhesion and other physical and chemical properties, and has low production cost; silica (SiO2) microspheres have the characteristics of controllable surface area, high mechanical strength, and stable thermal and physical and chemical properties. The control of silica surface structure can effectively increase the specific surface area of ​​microspheres, and has many micro-region-specific structural properties; chitosan (CS) has the advantages of wide availability, strong hydrophilicity, high metal ion binding activity, good biocompatibility, biodegradability and non-toxicity, and is an ideal adsorbent for organic synthesis catalysis. At the same time, chitosan has the advantages of Cu 2+ It has a high adsorption capacity and can achieve efficient catalysis under mild conditions, which is in line with the development concept of green chemistry.

[0009] PS-CS-SiO2@Cu catalytic material α , β , c , d -The chiral boron addition reaction of unsaturated ketones has high catalytic activity, and the catalytic material can be recycled and reused many times while maintaining excellent performance, which is very suitable for large-scale industrial applications.

[0010] Preferably, the reaction formula of the chiral boron addition reaction is:

[0011] R1 is selected from phenyl, 4-methylphenyl, 4-methoxyphenyl, 4-chlorophenyl, 4-nitrophenyl, 4-bromophenyl; R2 is selected from phenyl, 4-methylphenyl, 4-methoxyphenyl; R3 is selected from H atoms.

[0012] Preferably, α , β , c , d - Unsaturated ketones are selected from the following compounds: ; The corresponding 1,4-chiral boron compound is selected from the following compounds: .

[0013] Preferably, the chiral boron addition reaction comprises the following steps: S1, every 0.2mmol a,b,c,d -Add 0.24mmol B2(pin)2, 0.5-1.0mg chiral ligand, 2mL reaction solvent and 3-7mg nanocomposite microspheres loaded with copper material to the unsaturated ketone, stir at room temperature for 10-14h, and filter under reduced pressure to obtain a filtrate; S2, the filtrate was extracted with ethyl acetate and saturated brine in sequence, and then the organic phase was dried over anhydrous Na2SO4, filtered under reduced pressure and rotary dried to obtain a crude product; S3, purifying the crude product by thin layer chromatography to obtain 1,4-chiral boronate; S4. Wash the filter residue with petroleum ether, dry it in vacuum, and then recover the nanocomposite microsphere-loaded copper material for recycling.

[0014] Preferably, the reaction solvent is a toluene (TL)-H2O mixed solvent, and the volume ratio of TL to H2O in the TL-H2O mixed solvent is 5:5~1:9.

[0015] In the technical solution of the embodiment of the present application, toluene-water is selected as the reaction solvent. Water is green and environmentally friendly, has no environmental pollution, and acts as a protic solvent in the reaction process; the toluene solvent can help dissolve the organic reaction substrate and the Bolm Ligand chiral ligand in the reaction process. The mixed use of the two can accelerate the reaction process, is green and environmentally friendly, and also helps to separate the catalyst after the reaction is completed.

[0016] Preferably, the chiral ligand is Bolm Ligand, and the structural formula is: .

[0017] In the technical solution of the embodiment of the present application, the chiral ligand is a BolmLigand tetradentate ligand, which is beneficial to coordination with Cu during the reaction process and improves the chiral catalytic effect.

[0018] Preferably, the preparation method of the nanocomposite microsphere-loaded copper material comprises the following steps: P1. Prepare PS monodisperse microsphere powder in advance, add 0.8-1.0g hexadecyltrimethylammonium bromide, 100-150mL anhydrous ethanol and 80-120mL distilled water to every 0.8-1.2g PS monodisperse microsphere powder, stir for 0.2-0.5h, then add 0.5-1.0mL concentrated ammonia water and 0.5-0.8mL tetraethyl silicate, stir at room temperature for 4-8h, heat in an oil bath at 80°C for 10-18h, and vacuum dry at 40-60°C for 10-18h to obtain PS-SiO2 powder; P2, add 0.4~0.6g PS-SiO2 powder and 102mL 1~5% v / v acetic acid aqueous solution to every 0.8~1.2g chitosan to obtain system A; P3. Add 40-60 mL of anhydrous ethanol and 40-60 mL of distilled water to every 10.0-15.0 g of sodium hydroxide, stir until colorless and clear, and cool to room temperature to obtain system B; P4, adding system A dropwise into system B to form microspheres, filtering, washing with anhydrous ethanol, and drying at room temperature to obtain PS-CS-SiO2 nanocomposite microspheres; P5. Loading Cu on PS-CS-SiO2 nanocomposite microspheres 2+ , and obtained PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material.

[0019] In the technical solution of the embodiment of the present application, chitosan (CS) is used as the matrix, tetraethyl silicate (TEOS) is used as the silicon source, and cetyltrimethylammonium bromide (CTAB) is used as the surfactant to prepare PS-CS-SiO2 nanocomposite microspheres. The surface of the PS-CS-SiO2 nanocomposite microspheres contains abundant functional groups, such as amino groups and hydroxyl groups, so they can be well chelated with metals. The material can be combined with copper salts through coordination bonds, has good catalytic effects, and can be stably recycled.

[0020] The Si-OH functional groups on the surface of SiO2 can undergo condensation reaction with the amino groups of chitosan, so that chitosan is grafted on PS-SiO2 microspheres to form PS-CS-SiO2 nanocomposite microspheres, which produces more complexation sites and is convenient for subsequent coordination with copper ions; adding SiO2 to the catalytic material can form abundant Si-OH on the surface of PS microspheres, and the hardness of the material is enhanced, and the microsphere structure is more stable; chitosan is grafted on PS-SiO2 to form PS-CS-SiO2 nanocomposite microspheres, which have a stable structure, cheap raw materials and low preparation cost, and PS-CS-SiO2 nanocomposite microspheres are used as carriers to load copper acetate (Cu(OAc)2) by impregnation method to obtain polystyrene / chitosan / silica nanocomposite microspheres loaded with copper material (PS-CS-SiO2@Cu).

[0021] Preferably, the method for preparing the PS monodisperse microsphere powder in step P1 comprises the following steps: P11, add 2.0-2.5 g of polyvinyl pyrrolidone, 0.4-0.6 g of azobisisobutyronitrile, 20-40 mL of styrene, and 2-5 mL of distilled water to every 80-100 mL of anhydrous ethanol, perform ultrasonic dispersion at room temperature for 0.5-1 h, and stir at 60-100 °C for 18-30 h under inert gas protection to obtain a mixed solution; P12. The mixed solution was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol to obtain PS monodisperse microsphere powder.

[0022] In the technical scheme of the embodiment of the present application, the polystyrene / chitosan / silica nanocomposite microsphere loaded copper material (PS-CS-SiO2@Cu) provided by the present application uses styrene (St) as a monomer, polyvinyl pyrrolidone (PVP) as a surface stabilizer, growth modifier and dispersant, and azobisisobutyronitrile (AIBN) as an initiator to prepare PS monodisperse microsphere powder. The prepared PS monodisperse microsphere powder has a regular morphology and uniform microsphere particle size.

[0023] Preferably, the preparation method of PS-CS-SiO2@Cu nanocomposite microspheres in step P5 comprises the following steps: P51, placing the PS-CS-SiO2 nanocomposite microspheres obtained in step S4 in a water bath at 40-60°C for 1-2h to obtain system C; P52, add 3.0~5.0g of copper acetate to every 40~60mL of distilled water, stir at room temperature for 4~8h to obtain system D; P53. Stir and mix system C and system D, adsorb for 4 to 8 hours, filter, rinse with distilled water, and dry to obtain PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material.

[0024] In the technical solution of the embodiment of the present application, the PS-SiO2 nanocomposite microspheres have unique compatibility and spatial structure, and have a larger surface area than chitosan materials. Because chitosan is loaded on the surface of the PS-SiO2 microspheres, the PS-SiO2 microspheres have a larger specific surface area, and the chitosan is evenly dispersed on the surface of the PS-SiO2 microspheres, exposing more complexing sites, so the complexing ability for copper is significantly enhanced, and the contact with the reaction substrate is more sufficient, thereby having a higher catalytic activity when preparing chiral organic boron compounds; at the same time, since chitosan contains a large number of amino groups (-NH2), it provides an alkaline environment for the reaction, and can achieve catalytic reaction in a mixed solvent of organic reagent-water, which reduces the amount of organic reagent and alkali to a certain extent, in line with the concept of green chemistry development; in addition, the catalytic material can be recycled and reused many times while maintaining excellent performance, which is very suitable for large-scale industrial applications.

[0025] In a second aspect, the present invention provides a method for preparing a chiral hydroxy compound from a 1,4-chiral boride, comprising the following steps: (1) Add 240-250 mg of NaBO3·4H2O and 4-6 mL of a THF-H2O mixed solvent to the 1,4-chiral boride obtained in step S3, wherein the volume ratio of THF to H2O in the THF-H2O mixed solvent is 3:2, stir at room temperature for 3-6 h, extract with ethyl acetate and saturated brine in sequence, then dry the organic phase with anhydrous Na2SO4, filter under reduced pressure and spin dry; (2) The residue is spin-dried and purified by thin layer chromatography to obtain a chiral hydroxy compound.

[0026] Different from the existing technical solutions, the beneficial effects of this application include: 1. α , β , c , d -The chiral boron addition product of unsaturated ketone is an important biopharmaceutical intermediate and can be used as a raw material for preparing the anti-HIV drug (-)-equisetin. The present application uses a chiral ligand combined with a nanocomposite microsphere-loaded copper material as a catalyst in a reaction solvent. α , β , c , d -Chiral boron addition reaction of unsaturated ketones can successfully achieve a variety of α , β , c , d -Chiral boron addition of unsaturated ketone reaction substrates provides a new approach for the preparation of this type of biopharmaceuticals.

[0027] 2. In the present application, Bolm Ligand is used as a chiral ligand in combination with nanocomposite microspheres loaded with copper materials as catalyst in a TL-H2O reaction solvent. α , β , c , d -The chiral boron addition reaction of unsaturated ketones uses TL-H2O as the reaction solvent. H2O acts as a protic solvent during the reaction. TL helps dissolve the organic reaction substrate and the Bolm Ligand chiral ligand during the reaction, which can accelerate the chiral boron addition reaction. The use of this reaction solvent to prepare 1,4-chiral boron compounds has a higher yield and enantioselectivity.

[0028] 3. In this application, PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material are used as catalyst α , β , c , d -Chiral boron addition reaction of unsaturated ketones. The metal ion binding activity in the catalyst is high, and it can achieve efficient catalysis under mild conditions without adding additional additives. α , β , c , d The chiral boron addition reaction of unsaturated ketones is highly efficient, with a yield of up to 98% and an enantioselectivity of up to 96% for 1,4-chiral boron compounds.

[0029] 4. The PS-CS-SiO2@Cu nanocomposite microsphere-loaded copper material of the present application is a nanocomposite material, which has the characteristics of organic phase, inorganic phase and nanoparticles, and has the characteristics of small particle size, large specific surface area, strong adsorption, stable thermal and physical and chemical properties, etc.; compared with traditional Cu(II) homogeneous catalysts, the PS-CS-SiO2@Cu nanocomposite microsphere-loaded copper material of the present application can be recycled in a simple way, and has excellent reusability.

[0030] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 The infrared spectra of PS raw material, PS-CS-SiO2 nanocomposite microspheres and PS-CS-SiO2@Cu catalyst; Figure 2 This is the SEM image of the PS-CS-SiO2@Cu catalyst (magnification 8000 times). DETAILED DESCRIPTION

[0033] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0035] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0036] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0037] According to existing research reports, the effective boron addition α , β , c , d -Unsaturated ketones have fewer reaction substrates, and the chiral boron addition reactions reported so far are mostly homogeneously catalyzed. The catalysts are not biodegradable and recyclable, which does not conform to the development concept of green chemistry and is not suitable for large-scale industrial applications.

[0038] In order to solve the problem of effective boron addition α , β , c , d -Unsaturated ketone reaction substrate is small, and the catalyst cannot be recycled. This application provides a nanocomposite microsphere-loaded copper material catalytic α , β , c , d - a method for chiral boron addition reaction of unsaturated ketones, wherein, in a reaction solvent, α , β , c , d -Unsaturated ketone and B2(pin)2 undergo chiral boron addition reaction under the action of nanocomposite microspheres loaded with copper material and chiral ligand to obtain 1,4-chiral boron compound; the carrier of nanocomposite microspheres loaded with copper material is PS-CS-SiO2 nanocomposite microspheres, the PS-CS-SiO2 nanocomposite microspheres are composed of PS monodisperse microsphere powder, SiO2 and chitosan, and the active component Cu is loaded on the PS-CS-SiO2 nanocomposite microspheres 2+ , PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material were obtained; each 0.2mmol α , β , c , d -3~7 mg of nanocomposite microsphere-loaded copper material is added to the unsaturated ketone.

[0039] Preferably, the reaction formula of the chiral boron addition reaction is:

[0040] R1 is selected from phenyl, 4-methylphenyl, 4-methoxyphenyl, 4-chlorophenyl, 4-nitrophenyl, 4-bromophenyl; R2 is selected from phenyl, 4-methylphenyl, 4-methoxyphenyl; R3 is selected from H atoms.

[0041] Preferably, α , β , c , d -unsaturated ketone selected from (2 E ,4 E )-1,5-diphenylpenta-2,4-dien-1-one (molecular formula C 17 H 14 O)、(2 E ,4 E )-1-(4-methylphenyl)-5-phenylpenta-2,4-dien-1-one (molecular formula C 18 H 16 O)、(2 E ,4 E )-1-(4-methoxyphenyl)-5-phenylpenta-2,4-dien-1-one (molecular formula C 18 H 16 O2)、(2 E ,4 E )-1-(4-chlorophenyl)-5-phenylpenta-2,4-dien-1-one (molecular formula C 17 H 13 OCl)、(2 E ,4 E )-5-(4-methylphenyl)-1-phenylpenta-2,4-dien-1-one (molecular formula C 18 H 16 O), the structural formula is as follows: ; The corresponding 1,4-chiral boron compound is (3 S ,4 E )-1,5-diphenyl-3-boronic acid pinacol ester pent-4-en-1-one (molecular formula C 23 H 27 BO3)、(3 S ,4 E )-1-(4-methylphenyl)-5-phenyl-3-boronic acid pinacol ester pent-4-en-1-one (molecular formula C 24 H 29 BO3)、(3 S ,4E )-1-(4-methoxyphenyl)-5-phenyl-3-boronic acid pinacol ester pent-4-en-1-one (molecular formula C 24 H 29 BO4)、(3 S ,4 E )-1-(4-chlorophenyl)-5-phenyl-3-boronic acid pinacol ester pent-4-en-1-one (molecular formula C 23 H 26 BO3Cl)、(3 S ,4 E )-5-(4-methylphenyl)-1-phenyl-3-boronic acid pinacol ester pent-4-en-1-one (molecular formula C 24 H 29 BO3), the structural formula is as follows: .

[0042] Preferably, the chiral boron addition reaction comprises the following steps: S1, every 0.2mmol a,b,c,d -unsaturated ketone, add 0.24mmol B2(pin)2, 0.5~1.0mg chiral ligand, 2mL reaction solvent and 3~7mg nanocomposite microspheres loaded with copper material, stir at room temperature for 10~14h, and filter under reduced pressure to obtain a filtrate; PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper catalytic material, α , β , c , d -Unsaturated ketone, pinacol diboronate (B2(pin)2) and chiral ligand are dissolved in toluene (TL), stirred for a while and then distilled water is added; S2, the filtrate was extracted with ethyl acetate and saturated brine in sequence, and then the organic phase was dried over anhydrous Na2SO4, filtered under reduced pressure and rotary dried to obtain a crude product; S3. Purify the crude product by thin layer chromatography to obtain 1,4-chiral boronate.

[0043] Preferably, the reaction solvent is a toluene (TL)-H2O mixed solvent, wherein the volume ratio of TL to H2O in the TL-H2O mixed solvent is 5:5 to 1:9; S4. Wash the filter residue with petroleum ether (PE), dry it in vacuum, and then recover the nanocomposite microsphere-loaded copper material for recycling.

[0044] Preferably, the chiral ligand is Bolm Ligand, and the structural formula is: .

[0045] Preferably, the preparation method of the nanocomposite microsphere-loaded copper material comprises the following steps: P1. Prepare PS monodisperse microsphere powder in advance, add 0.8-1.0g hexadecyltrimethylammonium bromide, 100-150mL anhydrous ethanol and 80-120mL distilled water to every 0.8-1.2g PS monodisperse microsphere powder, stir for 0.2-0.5h, then quickly add 0.5-1.0mL concentrated ammonia water and 0.5-0.8mL tetraethyl silicate, stir at room temperature for 4-8h, heat in an oil bath at 80°C for 10-18h, and vacuum dry at 40-60°C for 10-18h to obtain PS-SiO2 powder; P2, add 0.4~0.6g PS-SiO2 powder and 102mL 1~5% v / v acetic acid aqueous solution to every 0.8~1.2g chitosan to obtain system A; P3. Add 40-60 mL of anhydrous ethanol and 40-60 mL of distilled water to every 10.0-15.0 g of sodium hydroxide, stir until colorless and clear, and cool to room temperature to obtain system B; P4, using a syringe to add system A drop by drop into system B to form microspheres, filtering, washing with anhydrous ethanol, and drying at room temperature to obtain PS-CS-SiO2 nanocomposite microspheres; P5. Loading Cu on PS-CS-SiO2 nanocomposite microspheres 2+ , and obtained PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material.

[0046] Preferably, the method for preparing the PS monodisperse microsphere powder in step P1 comprises the following steps: P11, add 2.0-2.5 g of polyvinyl pyrrolidone, 0.4-0.6 g of azobisisobutyronitrile, 20-40 mL of styrene, and 2-5 mL of distilled water to every 80-100 mL of anhydrous ethanol, perform ultrasonic dispersion at room temperature for 0.5-1 h, and stir at 60-100 °C for 18-30 h under inert gas protection to obtain a mixed solution; P12. The mixed solution was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol to obtain PS monodisperse microsphere powder.

[0047] Preferably, the preparation method of PS-CS-SiO2@Cu nanocomposite microspheres in step P5 comprises the following steps: P51, placing the PS-CS-SiO2 nanocomposite microspheres obtained in step S4 in a water bath at 40-60°C for 1-2h to obtain system C; P52, add 3.0~5.0g of copper acetate to every 40~60mL of distilled water, stir at room temperature for 4~8h to obtain system D; P53. Stir and mix system C and system D, adsorb for 4 to 8 hours, filter, rinse with distilled water, and dry to obtain PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material.

[0048] In a second aspect, the present invention provides a method for preparing a chiral hydroxy compound from a 1,4-chiral boride, comprising the following steps: (1) Add 240-250 mg of sodium borate tetrahydrate and 4-6 mL of a THF-H2O mixed solvent to the 1,4-chiral boride obtained in step S3, wherein the volume ratio of THF to H2O in the THF-H2O mixed solvent is 3:2, stir at room temperature for 3-6 h, extract with ethyl acetate and saturated brine in sequence, and then dry the organic phase with anhydrous Na2SO4, filter under reduced pressure, and spin dry; (2) The residue is spin-dried and purified by thin layer chromatography to obtain a chiral hydroxy compound.

[0049] In the technical solution of the embodiment of the present application, the reaction equation for preparing a chiral hydroxy compound from a 1,4-chiral boride is: ; The corresponding chiral hydroxy compound is (3 S ,4 E )-1,5-diphenyl-3-hydroxypent-4-en-1-one (molecular formula C 17 H 16 O2)、(3 S ,4 E )-1-(4-methylphenyl)-5-phenyl-3-hydroxypent-4-en-1-one (molecular formula C 18 H 18 O2)、(3 S ,4 E )-1-(4-methoxyphenyl)-5-phenyl-3-hydroxypent-4-en-1-one (molecular formula C 18 H 18 O3)、(3 S ,4 E )-1-(4-chlorophenyl)-5-phenyl-3-hydroxypent-4-en-1-one (molecular formula C 17 H 15 O2Cl)、(3 S ,4 E )-5-(4-methylphenyl)-1-phenyl-3-hydroxypent-4-en-1-one (molecular formula C 18 H 18 O2), the structural formula is as follows: .

[0050] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0051] 1. Preparation method Example 1 The preparation method of PS-CS-SiO2@Cu nanocomposite microsphere loaded copper material comprises the following steps: (1) Preparation of PS monodisperse microsphere powder S1, add 2.25g polyvinyl pyrrolidone, 0.5g azobisisobutyronitrile, 30mL styrene, 95mL anhydrous ethanol and 3mL distilled water into the reaction bottle, and ultrasonically disperse at room temperature for 0.5h; S2, under the protection of N2 inert gas, stir at 70°C for 24h; S3. Centrifuge and wash with anhydrous ethanol several times to obtain PS monodisperse microsphere powder.

[0052] (2) Preparation of PS-SiO2 powder S1. Add 1.0 g PS monodisperse microsphere powder, 0.92 g hexadecyltrimethylammonium bromide, 120 mL anhydrous ethanol and 100 mL distilled water to a reaction bottle, stir and dissolve for 20 min, then quickly add 0.8 mL concentrated ammonia and 0.6 mL tetraethyl silicate, stir at room temperature for 6 h, then transfer to an oil bath at 80 ° C and heat for 12 h to obtain a white suspension; S2. Filter under reduced pressure, wash with anhydrous ethanol several times, and vacuum dry at 50°C for 12 h to obtain PS-SiO2 white fluffy powder.

[0053] (3) Preparation of PS-CS-SiO2 nanocomposite microspheres S1, add 1.0 g chitosan (CS) powder, 0.5 g PS-SiO2 powder and 100 mL 1% v / v acetic acid aqueous solution into a reaction bottle to obtain system A; S2. Add 12.0 g of sodium hydroxide, 50 mL of anhydrous ethanol and 50 mL of distilled water to the reaction bottle, stir until colorless and clear, and cool to room temperature to obtain system B; S3. Use a syringe to drop system A into system B, filter through a mesh, wash with anhydrous ethanol for several times, and dry at room temperature to obtain PS-CS-SiO2 nanocomposite microspheres.

[0054] (4) Preparation of PS-CS-SiO2@Cu nanocomposite microspheres S1, placing 1.0 g of the obtained PS-CS-SiO2 nanocomposite microspheres in a reaction bottle in a water bath at 50°C for 1 h to obtain system C; S2. Add 3.7 g of copper acetate and 50 mL of distilled water to the reaction bottle and stir at room temperature for 6 h to obtain system D; S3. Stir and mix system C and system D, adsorb for 5 hours, filter through a mesh, rinse with distilled water, and dry at 50°C for 12 hours to obtain PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper.

[0055] Example 2 The PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper catalyst obtained in Example 1 were used a,b,c,d - Asymmetric boron addition reaction of unsaturated ketones, i.e. a,b,c,d -Unsaturated ketone and pinacol borate (B2(pin)2) undergo chiral boron addition reaction under the action of PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material and chiral ligand to obtain chiral boron compounds.

[0056] The reaction equation is:

[0057] In this embodiment a,b,c,d -The unsaturated ketone is (2E,4E)-1,5-diphenylpenta-2,4-diene-1-one, and the structural formula is as follows: ; The chiral ligand is a Bolm ligand, and the specific catalytic process is: S1. Add 46.9 mg (2E, 4E)-1,5-diphenylpenta-2,4-diene-1-one (Compound I-1), 60.9 mg pinacol diboron (B2(pin)2), 0.8 mg Bolm chiral ligand, 5 mg PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material and 2 mL reaction solvent into the reaction bottle. The reaction solvent is a mixture of methanol (TL) and water, TL:H2O=1:9. Stir at room temperature for 12 h. a,b,c,d -Asymmetric borylation of unsaturated ketones to obtain chiral boride (Compound I-2), the reaction equation is as follows:

[0058] S2. After the reaction is completed, the reaction is filtered under reduced pressure. The filtrate is extracted with ethyl acetate (EA) three times and saturated brine once. The organic phase is dried with anhydrous Na2SO4. The excess ethyl acetate (EA) is removed by filtering with a sand core funnel under reduced pressure and rotary drying. The crude product is purified by thin layer chromatography (TLC) to obtain a chiral organic boron compound (Compound I-2) with the following structural formula: ; S3, add 244 mg of sodium borate tetrahydrate (NaBO3·4H2O) and 5 mL of THF-H2O (V:V=3:2) mixed solvent to the chiral organic boron compound (Compound I-2) obtained in step S2 above, and stir at room temperature for 4 h; S4. After the above reaction is completed, the mixture is extracted with ethyl acetate (EA) three times and saturated brine once, and the organic phase is dried with anhydrous Na2SO4. The excess ethyl acetate (EA) is removed by vacuum filtration using a sand core funnel and then rotary drying. The spin-dried residue is then purified by thin layer chromatography (TLC) to obtain a chiral hydroxy compound (Compound I-3) for determining enantioselectivity and stereochemical configuration. The reaction equation is as follows: .

[0059] Example 3 The difference between Example 3 and Example 2 is that the method used in step S1 is a,b,c,d -unsaturated ketone reaction substrate is different, the other steps are the same. a,b,c,d -Unsaturated ketone structural formula is as follows: , The chiral ligand is a Bolm ligand, and the catalytic process is: S1. Add to the reaction bottle α , β , c , d -unsaturated ketone, pinacol borate (B2(pin)2), Bolm chiral ligand, PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material and reaction solvent, stirred at room temperature for 12h, and the reaction occurred. a,b,c,d -Asymmetric borylation of unsaturated ketones to obtain chiral boride with the following structural formula: .

[0060] Example 4 The difference between Example 4 and Example 2 is that the method used in step S1 is a,b,c,d -unsaturated ketone reaction substrate is different, the other steps are the same. a,b,c,d -Unsaturated ketone structural formula is as follows: , The chiral ligand is a Bolm ligand, and the catalytic process is: S1. Add to the reaction bottle α , β , c , d-unsaturated ketone, pinacol borate (B2(pin)2), Bolm chiral ligand, PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material and reaction solvent, stirred at room temperature for 12h, and the reaction occurred. a,b,c,d -Asymmetric borylation of unsaturated ketones to obtain chiral boride with the following structural formula: .

[0061] Example 5 The difference between Example 5 and Example 2 is that the method used in step S1 is a,b,c,d -unsaturated ketone reaction substrate is different, the other steps are the same. a,b,c,d -Unsaturated ketone structural formula is as follows: , The chiral ligand is a Bolm ligand, and the catalytic process is: S1. Add to the reaction bottle α , β , c , d -unsaturated ketone, pinacol borate (B2(pin)2), Bolm chiral ligand, PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material and reaction solvent, stirred at room temperature for 12h, and the reaction occurred. a,b,c,d -Asymmetric borylation of unsaturated ketones to obtain chiral boride with the following structural formula: .

[0062] Example 6 The difference between Example 6 and Example 2 is that the method used in step S1 is a,b,c,d -unsaturated ketone reaction substrate is different, the other steps are the same. a,b,c,d -Unsaturated ketone structural formula is as follows: , The chiral ligand is a Bolm ligand, and the catalytic process is: S1. Add to the reaction bottle a,b,c,d -unsaturated ketone, pinacol borate (B2(pin)2), Bolm chiral ligand, PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material and reaction solvent, stirred at room temperature for 12h, and the reaction occurred. a,b,c,d -Asymmetric borylation of unsaturated ketones to obtain chiral boride with the following structural formula: .

[0063] Example 7 The difference between Example 7 and Example 2 is that in Example 7, the filter residue obtained by vacuum filtration in step S2 of Example 2 is washed with petroleum ether (PE) three times, vacuum dried at 50°C for 12 h to remove the petroleum ether (PE), and the PS-CS-SiO2@Cu catalytic material is recovered for recycling. The number of cycles of the PS-CS-SiO2@Cu catalytic material used in Example 7 is 1, and the other steps are the same as those in Example 2.

[0064] Example 8 The difference between Example 8 and Example 2 is that in Example 8, the filter residue obtained by vacuum filtration in step S2 of Example 2 is washed with petroleum ether (PE) three times, vacuum dried at 50°C for 12 h to remove the petroleum ether (PE), and the PS-CS-SiO2@Cu catalytic material is recovered and recycled. The PS-CS-SiO2@Cu catalytic material used in Example 8 is recycled twice, and the other steps are the same as in Example 2.

[0065] Example 9 The difference between Example 9 and Example 2 is that in Example 9, the filter residue obtained by vacuum filtration in step S2 of Example 2 is washed with petroleum ether (PE) three times, vacuum dried at 50°C for 12 h to remove the petroleum ether (PE), and the PS-CS-SiO2@Cu catalytic material is recovered and recycled. The PS-CS-SiO2@Cu catalytic material used in Example 9 is recycled three times, and the other steps are the same as in Example 2.

[0066] Example 10 The difference between Example 10 and Example 2 is that in Example 10, the filter residue obtained by vacuum filtration in step S2 of Example 2 is washed with petroleum ether (PE) three times, vacuum dried at 50°C for 12 h to remove the petroleum ether (PE), and the PS-CS-SiO2@Cu catalytic material is recovered and recycled. The number of cycles of the PS-CS-SiO2@Cu catalytic material used in Example 10 is 4 times, and the other steps are the same as those in Example 2.

[0067] Embodiment 11 The difference between Example 11 and Example 2 is that in Example 11, the filter residue obtained by vacuum filtration in step S2 of Example 2 is washed with petroleum ether (PE) three times, vacuum dried at 50°C for 12 h to remove the petroleum ether (PE), and the PS-CS-SiO2@Cu catalytic material is recovered and recycled. The PS-CS-SiO2@Cu catalytic material used in Example 11 is recycled five times, and the other steps are the same as those in Example 2.

[0068] Example 12 The difference between Example 12 and Example 2 is that in step S1 of Example 12, the amount of copper material loaded on PS-CS-SiO2@Cu nanocomposite microspheres is 3 mg, and the other steps are the same as those in Example 2.

[0069] Embodiment 13 The difference between Example 13 and Example 2 is that in step S1 of Example 13, the amount of copper material loaded in PS-CS-SiO2@Cu nanocomposite microspheres is 7 mg, and the other steps are the same as those in Example 2.

[0070] Embodiment 14 The difference between Example 14 and Example 2 is that in step S1 of Example 14, the reaction solvent is a mixture of methanol (TL) and water, TL:H2O=5:5, and the other steps are the same as those of Example 2.

[0071] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the catalyst used in step S1 is different, and the other steps are the same. Comparative Example 1 uses inorganic copper salt Cu(OAc)2 as a catalyst for a,b,c,d -Asymmetric boron addition reaction of unsaturated ketones, the specific catalytic process is: S1. Add 46.9 mg (2E,4E)-1,5-diphenylpenta-2,4-diene-1-one (Compound I-1), 60.9 mg of biboric acid pinacol ester (B2(pin)2), 0.8 mg of Bolm chiral ligand, 0.8 mg of Cu(OAc)2 catalyst and 2 mL of reaction solvent to the reaction bottle and stir at room temperature for 12 h. a,b,c,d -Asymmetric borylation of unsaturated ketones to give chiral boride (Compound I-2).

[0072] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that in step S1 of Comparative Example 2, the amount of copper material loaded on PS-CS-SiO2@Cu nanocomposite microspheres is 1 mg, and the other steps are the same as those of Example 2.

[0073] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that in step S1 of Comparative Example 3, the reaction solvent is a mixture of tetrahydrofuran (THF) and water, THF:H2O=1:9, and the other steps are the same as those of Example 2.

[0074] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that in step S1 of Comparative Example 4, the reaction solvent is a mixture of methanol (MeOH) and water, MeOH:H2O=1:9, and the other steps are the same as those of Example 2.

[0075] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that in step S1 of Comparative Example 5, the reaction solvent is a mixture of acetic acid (Ac) and water, Ac:H2O=1:9, and the other steps are the same as those of Example 2.

[0076] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that in step S1 of Comparative Example 6, the reaction solvent is a mixture of dimethylacetamide (DMF) and water, DMF:H2O=1:9, and the other steps are the same as those of Example 2.

[0077] 2. Test Method Yield and enantioselectivity (ee value) detection method of chiral organic boron compound: The crude product of chiral organic boron compound is oxidized by sodium perborate tetrahydrate oxidation system to obtain hydroxyl compound for separation, and finally the final product is obtained by column chromatography, and its structure and yield are determined by nuclear magnetic resonance, and then its enantioselectivity is tested by liquid chromatography analyzer.

[0078] 3. Analysis of test results of various embodiments and comparative examples.

[0079] (1) The PS monodisperse microsphere powder, PS-CS-SiO2 nanocomposite microspheres and PS-CS-SiO2@Cu nanocomposite microspheres prepared in Example 1 were subjected to infrared spectrum scanning, and the PS-CS-SiO2@Cu nanocomposite microspheres were subjected to SEM scanning.

[0080] Figure 1 The infrared spectra of PS raw material, PS-CS-SiO2 nanocomposite microspheres and PS-CS-SiO2@Cu catalyst; compared with the infrared spectrum of PS, some new absorption peaks appeared in the infrared spectrum of PS-CS-SiO2. 740cm -1 The symmetrical stretching vibration absorption peak of Si-C is 438 cm -1 The absorption peak of Si-O-Si bending vibration is at 1551cm, which can confirm the successful preparation of PS-CS-SiO2 microspheres. -1 It is the vibration absorption peak of the amide II group in chitosan, 1046cm -1 The peaks at the bottom are the stretching vibration absorption peaks and bending vibration absorption peaks of the CH bond of copper acetate. It can be seen that copper ions are successfully loaded on the PS-CS-SiO2 microspheres.

[0081] The prepared PS-CS-SiO2@Cu nanocomposite microspheres are Figure 2 As shown in the figure, it can be seen that the morphology of the chitosan-based silica microspheres can be well maintained, and loaded particles, namely copper ion loads, can be seen on the surface.

[0082] (2) The PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper obtained in Example 1 and the conventional inorganic copper salt catalyst in Comparative Example 1 were used to a,b,c,d -Unsaturated ketone asymmetric boron addition reaction was compared, and the results are shown in Table 1 below: Table 1 New catalysts and inorganic copper salts a,b,c,d -Comparison of Asymmetric Boron Addition Reactions of Unsaturated Ketones

[0083] As can be seen from Table 1, the new catalytic material PS-CS-SiO2@Cu catalyzes a,b,c,d - The effect of asymmetric boron addition reaction of unsaturated ketone is better than that of traditional inorganic copper salt Cu(OAc)2. The main reason is that the contact area between PS-CS-SiO2@Cu and organic substrate is better than that of Cu(OAc)2. The catalytic material PS-CS-SiO2@Cu prepared in Example 1 is used as catalyst a,b,c,d -The yield of the asymmetric boron addition reaction of unsaturated ketones is as high as 98%, and the ee value is as high as 96%; it is worth mentioning that the new catalytic material PS-CS-SiO2@Cu is recyclable and green and environmentally friendly.

[0084] (3) Examples 2 to 6 are about using the PS-CS-SiO2@Cu catalytic material obtained in Example 1 for various a,b,c, d -Unsaturated ketone reaction substrate asymmetric boron addition reaction, the results are shown in Table 2 below: Table 2 Yields and enantioselectivities of chiral organoboron compounds prepared from different reaction substrates

[0085] From the data in Table 2, it can be seen that the PS-CS-SiO2@Cu catalyst prepared in Example 1 has excellent universality through the extended substrate test. E ,4 E )-1,5-diphenylpenta-2,4-diene-1-one (compound I-1), the yield (yield) was as high as 98%, and the enantioselectivity (ee value) was as high as 96%. E ,4 E )-1-(4-methylphenyl)-5-phenylpenta-2,4-diene-1-one (Compound II-1), the yield (yield) was as high as 91%, and the enantioselectivity (ee value) was as high as 93%. E ,4 E)-1-(4-methoxyphenyl)-5-phenylpenta-2,4-diene-1-one (Compound III-1), the yield (yield) was as high as 95%, and the enantioselectivity (ee value) was as high as 94%. E ,4 E )-1-(4-chlorophenyl)-5-phenylpenta-2,4-diene-1-one (compound IV-1), the yield (yield) was as high as 91%, and the enantioselectivity (ee value) was as high as 95%. E ,4 E )-5-(4-methylphenyl)-1-phenylpenta-2,4-diene-1-one (compound V-1), the yield (yield) was as high as 89%, and the enantioselectivity (ee value) was as high as 92%. In summary, the PS-CS-SiO2@Cu catalyst prepared in Example 1 is effective for a,b,c,d -Unsaturated ketones are generally applicable to chiral asymmetric boron addition reactions.

[0086] (4) In Example 2, the PS-CS-SiO2@Cu catalyst was recycled for 0 times. In Examples 7 to 11, the PS-CS-SiO2@Cu catalyst was recycled for 1, 2, 3, 4 and 5 times, respectively, to investigate the performance of the recycled catalyst. The yield (yield) and enantioselectivity (ee value) of the chiral organoboron compound finally prepared are shown in Table 3: Table 3 Effect of catalyst recycling times on the yield and enantioselectivity of organic boron compounds

[0087] From the data in Table 3, it can be seen that when the reaction time, reaction solvent and catalyst dosage are consistent, the number of catalyst recycling times is a,b,c,d -The yield (yield) and enantioselectivity (ee value) of the chiral asymmetric boron addition reaction of unsaturated ketones were almost unaffected. The yield (yield) and enantioselectivity (ee value) of the catalyst that was not recycled and the catalyst that was recycled 5 times were both over 90%, and almost completely converted. This shows that the catalytic effect of the recycled catalyst is still significant, and the performance of the recycled catalyst is good, achieving the purpose of recycling, saving costs and responding to the concept of green chemistry development.

[0088] (5) In Example 2, the amount of copper material loaded on PS-CS-SiO2@Cu nanocomposite microspheres was 5 mg. In Comparative Example 2, Examples 12 and 13, the amount of catalyst was 1 mg, 3 mg and 7 mg, respectively, to investigate the effect of the amount of catalyst on the catalytic performance. The yield (yield) and enantioselectivity (ee value) of the chiral organic boron compound finally prepared are shown in Table 4: Table 4 Effect of catalyst dosage on the yield and enantioselectivity of organic boron compounds

[0089] It can be seen from Table 4 that when the catalyst dosage is 3-7 mg, the yield (yield) and enantioselectivity (ee value) of the prepared chiral organic boron compound are high. When the catalyst dosage is 1 mg, the yield of the chiral organic boron compound is low due to the small amount of catalyst.

[0090] (6) In Example 2, the reaction solvent is a mixture of toluene (TL) and water, TL:H2O=1:9, and in Example 14, the reaction solvent is a mixture of toluene (TL) and water, TL:H2O=5:5. Comparative Examples 3 to 6 use different reaction solvents, and the reaction solvents used are THF:H2O=1:9, MeOH:H2O=1:9, Ac:H2O=1:9 and DMF:H2O=1:9, respectively, to investigate the effect of solvent type on catalytic performance. The yield (yield) and enantioselectivity (ee value) of the chiral organoboron compound finally prepared are shown in Table 5: Table 5 Effect of reaction solvent type on the yield and enantioselectivity of the preparation of organoboron compounds

[0091] As can be seen from Table 5, when TL-H2O is used as the reaction solvent, the yield of the chiral organic boron compound prepared when TL:H2O=1:9 can reach 98%, which can almost achieve complete conversion, and the enantioselectivity (ee value) is 96%. When other types of reaction solvents are used, the yield and enantioselectivity are lower.

[0092] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. Nanocomposite microspheres loaded with copper materials for catalysis α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that: The method comprises the following steps: in a reaction solvent, α , β , γ , δ -unsaturated ketone and B2(pin)2 undergo chiral boron addition reaction under the action of nanocomposite microspheres loaded with copper material and chiral ligands to obtain 1,4-chiral boron compounds; the carrier of the nanocomposite microspheres loaded with copper material is PS-CS-SiO2 nanocomposite microspheres, the PS-CS-SiO2 nanocomposite microspheres are composed of PS monodisperse microsphere powder, SiO2 and chitosan, and the PS-CS-SiO2 nanocomposite microspheres are loaded with active components Cu 2+ , PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material were obtained; each 0.2mmol α , β , γ , δ -3~7 mg of nanocomposite microsphere-loaded copper material is added to the unsaturated ketone.

2. The nanocomposite microsphere-supported copper material catalyst according to claim 1 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that The reaction equation for the chiral boron addition reaction is: R1 is selected from phenyl, 4-methylphenyl, 4-methoxyphenyl, 4-chlorophenyl, 4-nitrophenyl, 4-bromophenyl; R2 is selected from phenyl, 4-methylphenyl, 4-methoxyphenyl; R3 is selected from H atoms.

3. The nanocomposite microsphere-supported copper material catalyst according to claim 1 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that: Said α , β , γ , δ - Unsaturated ketones are selected from the following compounds: ; The corresponding 1,4-chiral boron compounds are as follows: 。 4. The nanocomposite microsphere-supported copper material catalyst according to claim 1 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that The chiral boron addition reaction includes the following steps: S1, every 0.2mmol α,β,γ,δ -Add 0.24mmol B2(pin)2, 0.5-1.0mg chiral ligand, 2mL reaction solvent and 3-7mg nanocomposite microspheres loaded with copper material to the unsaturated ketone, stir at room temperature for 10-14h, and filter under reduced pressure to obtain a filtrate and a filter residue; S2, the filtrate was extracted with ethyl acetate and saturated brine in sequence, and then the organic phase was dried over anhydrous Na2SO4, filtered under reduced pressure and rotary dried to obtain a crude product; S3, purifying the crude product by thin layer chromatography to obtain 1,4-chiral boronate; S4. Wash the filter residue with petroleum ether, dry it in vacuum, and then recover the nanocomposite microsphere-loaded copper material for recycling.

5. The nanocomposite microsphere-supported copper material catalyzer according to any one of claims 1 to 4 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that The reaction solvent is a TL-H2O mixed solvent, and the volume ratio of TL to H2O in the TL-H2O mixed solvent is 5:5~1:

9.

6. The nanocomposite microsphere-supported copper material catalyzer according to any one of claims 1 to 4 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that The chiral ligand is Bolm Ligand, and its structural formula is: 。 7. The nanocomposite microsphere-supported copper material catalyzer according to any one of claims 1 to 4 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that The preparation method of the nanocomposite microsphere-loaded copper material comprises the following steps: P1. Prepare PS monodisperse microsphere powder in advance, add 0.8-1.0 g of hexadecyltrimethylammonium bromide, 100-150 mL of anhydrous ethanol and 80-120 mL of distilled water to every 0.8-1.2 g of PS monodisperse microsphere powder, stir for 0.2-0.5 h, then add 0.5-1.0 mL of concentrated ammonia water and 0.5-0.8 mL of tetraethyl silicate, stir at room temperature for 4-8 h, heat in an oil bath at 80 ° C for 10-18 h, and vacuum dry at 40-60 ° C for 10-18 h to obtain PS-SiO2 powder; P2, add 0.4~0.6g PS-SiO2 powder and 102mL 1~5% v / v acetic acid aqueous solution to every 0.8~1.2g chitosan to obtain system A; P3. Add 40-60 mL of anhydrous ethanol and 40-60 mL of distilled water to every 10.0-15.0 g of sodium hydroxide, stir until colorless and clear, and cool to room temperature to obtain system B; P4, adding system A dropwise into system B to form microspheres, filtering, washing with anhydrous ethanol, and drying at room temperature to obtain PS-CS-SiO2 nanocomposite microspheres; P5. Loading Cu on PS-CS-SiO2 nanocomposite microspheres 2+ , and obtained PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material.

8. The nanocomposite microsphere-supported copper material catalyst according to claim 7 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that: The method for preparing the PS monodisperse microsphere powder in step P1 comprises the following steps: P11, add 2.0-2.5 g of polyvinyl pyrrolidone, 0.4-0.6 g of azobisisobutyronitrile, 20-40 mL of styrene, and 2-5 mL of distilled water to every 80-100 mL of anhydrous ethanol, perform ultrasonic dispersion at room temperature for 0.5-1 h, and stir at 60-100 °C for 18-30 h under inert gas protection to obtain a mixed solution; P12. The mixed solution was centrifuged to obtain a precipitate, and the precipitate was washed with anhydrous ethanol to obtain PS monodisperse microsphere powder.

9. The nanocomposite microsphere-supported copper material catalyst according to claim 7 α , β , γ , δ - A method for chiral boron addition reaction of unsaturated ketones, characterized in that: The preparation method of PS-CS-SiO2@Cu nanocomposite microspheres in step P5 comprises the following steps: P51, placing the PS-CS-SiO2 nanocomposite microspheres obtained in step S4 in a water bath at 40-60°C for 1-2h to obtain system C; P52, add 3.0~5.0g of copper acetate to every 40~60mL of distilled water, stir at room temperature for 4~8h to obtain system D; P53. Stir and mix system C and system D, adsorb for 4 to 8 hours, filter, rinse with distilled water, and dry to obtain PS-CS-SiO2@Cu nanocomposite microspheres loaded with copper material.

10. The method for preparing a chiral hydroxy compound from a 1,4-chiral boride according to any one of claims 1 to 4, characterized in that: The steps include: (1) Add 240-250 mg of NaBO3·4H2O and 4-6 mL of a THF-H2O mixed solvent to the 1,4-chiral boride obtained in step S3, wherein the volume ratio of THF to H2O in the THF-H2O mixed solvent is 3:2, stir at room temperature for 3-6 h, extract with ethyl acetate and saturated brine in sequence, then dry the organic phase with anhydrous Na2SO4, filter under reduced pressure and spin dry; (2) The residue is spin-dried and purified by thin layer chromatography to obtain a chiral hydroxy compound.